South-Western Federal Taxation 2021: Comprehensive, 44th Edition - David M. Maloney; James C. Young; Annette Nellen (Cengage Learning, 2020)
Gain a thorough understanding of today's tax concepts and current tax law with SOUTH-WESTERN FEDERAL TAXATION 2021: COMPREHENSIVE, 44E. This reader-friendly presentation emphasizes the latest tax law and recent changes impacting individuals, corporations, partnerships, estates and trusts and financial statements. You examine tax law changes as recent as 2020 with complete coverage of the Tax Cuts and Jobs Act of 2017 and related guidance from the Treasury Department. Clear examples, frequent summaries and interesting tax scenarios clarify concepts and sharpen your critical-thinking, writing and research skills. Discover how an understanding of today's taxes can benefit you as you prepare for the C.P.A. or the Enrolled Agent exam or pursue a career in tax accounting, financial reporting or auditing. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.